Method for testing, evaluating and regulating electron transmission performance of supported metal catalyst

The volume resistivity of the conductive glue is measured by a four-probe tester, and combined with the oxidation treatment to regulate the electronic structure of the catalyst, the problem of difficult to detect the electronic transmission performance of the loaded metal catalyst in the prior art is solved, and high-precision evaluation and performance regulation are achieved.

CN119716325APending Publication Date: 2025-03-28UNIV OF SHANGHAI FOR SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411866766.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to directly and accurately detect and evaluate the electron transport performance of loaded metal catalysts, especially in the case of support non-conductor materials and low loading, with large measurement errors and limited applicability.

Method used

The volume resistivity of the conductive glue is measured by using a four-probe tester, and the electrical conductivity of the catalyst is regulated by uniformly dispersing the supported metal catalyst in the conductive glue, and oxidation treatment is used to regulate the electronic structure of the catalyst.

Benefits of technology

High-precision evaluation of the electronic transmission performance of supported metal catalysts is achieved, measurement errors are reduced, suitable for various material forms, and the electrical conductivity of the catalyst is improved by regulating the electronic structure of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119716325A_ABST
    Figure CN119716325A_ABST
Patent Text Reader

Abstract

The invention discloses a method for testing, evaluating and regulating the electron transmission performance of a supported metal catalyst, and belongs to the technical field of electrical property detection. According to the method, the conductive adhesive is taken as a carrier, catalyst powder is introduced into the carrier, then conductive filler, a resin matrix and a catalyst are uniformly mixed, after the conductive adhesive (ECAs) is formed according to a conductive silver paste curing procedure, the volume resistivity rho of the conductive adhesive is tested by using a four-probe tester, and the electronic transmission performance of different supported catalysts can be evaluated. The method has the advantages of simple operation, stable test result and small error range, is suitable for testing and evaluating the conductivity of various forms of catalyst materials (such as particles, films and composite materials), can provide a high-precision conductivity measurement result, and helps to understand the electron transfer mechanism process of the supported metal catalyst; in addition, the invention also provides a scheme for regulating and controlling the conductivity of the catalyst by regulating and controlling the electronic structure of the active center of the catalyst through oxidation treatment of the catalyst material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrical performance detection, and in particular to a method for testing, evaluating and regulating the electronic transmission performance of a supported metal catalyst. Background Art

[0002] Catalyst materials and catalytic reaction processes are important components of the modern chemical industry, and supported metal catalysts are one of the important research contents in the field of science and technology. With the development of green chemistry and new energy sources, the development and application of new functional catalysts have always attracted much attention in the fields of biomass energy catalytic conversion, fuel cells, water electrolysis hydrogen production and environmental purification. At the same time, with the development of nanotechnology, the design and development of supported metal catalysts have become more and more sophisticated. Researchers continue to explore different types of carrier materials (such as carbon materials, metal oxides, molecular sieve materials, etc.) and supported metal active centers, design and construct different spatial structures to improve the performance of catalysts (activity, selectivity, stability). Among them, the chemical element composition, electronic structure, particle size, morphology, dispersion of active centers, surface adsorption and desorption, and spatial structure of the catalyst are key factors that determine the performance of the catalyst.

[0003] Catalytic reactions generally involve three main steps: "adsorption-reaction-desorption". Reactant molecules are generally adsorbed through the interaction between functional groups and the active sites of the catalyst or the adsorption sites of the carrier. When these reactant molecules enriched around the active center reach a certain concentration, they will collide effectively and be activated, thereby undergoing a chemical reaction, and the generated products will desorb from the active sites. In this process, especially in redox reactions, the electronic structure of the metal active sites (such as valence state, charge density, electron migration, micro-interface environment of the contact carrier, etc.) plays a decisive role in the efficiency of adsorption and activation of reactant molecules. This is because the electronic structure of the metal active sites can determine the "interaction and competition relationship" and "electron transfer direction and rate" between them and the reaction molecules, and then determine the precise activation and directional conversion of the functional groups in the molecules. This link is often the rate-controlling step of the catalytic reaction process and directly determines the catalytic activity or selectivity. Therefore, it is particularly important to develop methods to directly detect and accurately regulate the electron transfer rate of supported metal catalysts. The establishment of a method for quantitatively detecting and evaluating the electron transport performance of supported metal catalysts is very helpful for researchers to understand the electron transfer mechanism of catalysts during the reaction process and to reveal the mechanism and reaction pathway of catalytic reactions, which are also the basic principles of catalytic science.

[0004] Electron transport refers to the process of electron movement, migration, and transmission in different substances. For conductive materials, electrons can move freely in them, and the basic concepts of electron transport performance include current, conductivity, and resistivity. When detecting the electronic properties of solid catalysts, commonly used experimental methods include electrochemical testing, spectroscopic methods, and kinetic studies. Electrochemical testing can directly measure the electron transfer rate of catalysts in electrochemical reactions, providing important data in dynamic reaction environments. Spectroscopic methods, such as Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy (Raman), can reveal the changes in functional groups and the existence of intermediates during the catalyst reaction process, helping to understand the mechanism of electron interaction and transfer. Kinetic studies focus on reaction rates and control mechanisms, and by analyzing the effect of reactant concentration on reaction rates, the amount, direction, and control steps of electron transfer can be inferred. Although the above methods can provide rich information about the electron transfer process, they are often limited by their respective reaction equipment, catalyst material morphology, and reaction type, and cannot directly evaluate the electron transfer performance of supported metal catalysts in different applications. For example, when the metal active site loading is low and the carrier is a non-conducting material, it is very difficult to directly measure its resistivity or current; for another example, the electrochemical workstation is suitable for electrocatalytic systems, but not for photocatalysts and traditional heat-driven catalyst systems, and does not involve direct detection of the electron transfer rate of solid catalysts.

[0005] Chinese patent CN103852642A discloses a method for detecting trace solid conductivity, which uses two metal nail-shaped electrodes to confine the test powder in a polytetrafluoroethylene pressure tube with a height of 1 to 3 cm and a diameter of 3 to 5 mm; during measurement, pressure is applied to the metal nail-shaped electrodes at both ends to expel the air between the powders and squeeze them into a cylindrical shape; the length of the cylinder can be measured by a measuring tool, and the overall resistance can be measured by a multimeter to calculate the conductivity. This method can maintain the original properties of the powder, can use trace amounts of samples, and obtain accurate conductivity measurement data without adding any liquid additives or changing any properties of the powder. However, most supported metal catalyst carriers such as TiO 2 、ZrO 2 、Al 2 O 3 , activated carbon, molecular sieves, MOFs, etc. are not intrinsic conductors, and the gaps between particles are large. Even if compacted, the internal gaps still occupy a certain proportion. These will bring large measurement errors, so the scope of use of this method is limited.

[0006] Some schemes for measuring the electrical conductivity of materials have also been reported in the prior art, such as a method for measuring the electrical conductivity of MOFs materials (Harnessing Electrostatic Interactions for Enhanced Conductivity in Metal-Organic Frameworks, Research, 2021, 9874273), a method for in situ measuring the electrical conductivity of powdered catalysts under different atmospheric conditions (Electrical conductivity of a MoVTeNbO catalyst inpropene oxidation measured in operando conditions, Catalysis Today 155 (2010) 311-318), and a method for testing the electrical conductivity of solid catalysts (Oxidative coupling of methane over (Na 2 WO 4 +Mn or Ce) / SiO 2 catalysts: In situ measurement of electrical conductivity, Journal of Natural Gas Chemistry 19 (2010) 35–42). Among them, the scheme for measuring the electrical conductivity of MOFs materials requires that the powder sample be pressed into microspheres or pellets for measurement. This is similar to the scheme disclosed in patent CN103852642A. Although this scheme can maintain the original shape of the powder, for catalyst carriers that are not intrinsic conductors, the gap between the particles is large after being pressed into microspheres or pellets, which will cause a large measurement error. The overall design of the latter two schemes is similar. The advantages of these two schemes are that they can detect the relationship between the change of the conductivity of the catalyst under in-situ conditions (reaction temperature and atmosphere, etc.), but the disadvantages are that the errors caused by the catalyst loading and compaction sample preparation process are large, and the corresponding devices are mainly suitable for gas-solid phase reaction systems, and there will be great difficulties in using them in liquid-solid phase reaction systems. At the same time, the implementation of these two schemes requires relatively complex experimental settings and a long data collection process, and the operability is relatively low, and the use is also limited.

[0007] The four-probe tester is a multi-purpose comprehensive measuring device that uses the four-probe measurement principle. It is a special instrument used to test the resistivity and sheet resistance (sheet resistance) of semiconductor materials. It has the characteristics of fast measurement, high accuracy, wide measurement range, good stability, and almost no strict requirements on the geometric dimensions of the sample. If the four-probe tester can be used to effectively detect the resistivity of supported metal catalysts, it is expected to open up new research ideas and methods for the exploration of catalytic reaction mechanisms and the design of new materials. Summary of the invention

[0008] The purpose of the present invention is to solve the problems existing in the prior art, and provide a method for evaluating the electron transport performance of a supported metal catalyst by testing the volume resistivity ρ of a cured conductive adhesive based on a four-probe tester, and on this basis, a method for regulating the electronic structure of the active center of the catalyst by an oxidation treatment method is proposed, thereby regulating the conductive performance of the catalyst.

[0009] In order to achieve the above technical objectives, the present invention is implemented by the following technical solutions:

[0010] A method for testing and evaluating the electron transport performance of a supported metal catalyst comprises the following steps:

[0011] 1) preparing a resin matrix;

[0012] 2) preparing a conductive adhesive: adding a conductive filler into the resin matrix prepared in step 1) and grinding;

[0013] 3) adding a supported metal catalyst to the conductive adhesive and grinding it, coating it evenly on a glass slide, heating and curing it, and cooling it to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0014] 4) Volume resistivity measurement: The thickness of the conductive glue was measured, and the volume resistivity ρ (GB / T 31838.2-2019) of the conductive glue was tested using an ST-2258C multifunctional digital four-probe tester for analysis and comparison to evaluate the electron transport performance of different supported catalysts.

[0015] Furthermore, in step 1), the resin matrix is ​​obtained by uniformly mixing a resin raw material, a curing agent and a coupling agent, and the resin raw material is one or more of epoxy resin, silicone resin, acrylic resin and phenolic resin.

[0016] Furthermore, in step 2), the mass ratio of the resin matrix to the conductive filler is 1-4:6-9, and the conductive filler used is any one or more of silver, gold, nickel, copper, aluminum, tin, lead, indium, zinc, and iron, preferably silver powder, and the silver powder particle size is 1-3 μm.

[0017] Furthermore, in step 3), after the supported metal catalyst is added to the conductive silver paste, the weight percentage of the supported metal catalyst is 1 to 10 wt %, preferably 5 wt %.

[0018] Furthermore, in step 3), the grinding time is 10 to 20 minutes, the heating and curing temperature is 170 to 180° C., and the heating and curing time is 60 minutes.

[0019] Furthermore, in step 3), the method for regulating the electron transport performance of the supported metal catalyst is to perform an oxidation treatment on the supported metal catalyst, wherein the oxidation treatment comprises using H 2 O 2 Oxidation, O 2 Oxidation or air oxidation.

[0020] Furthermore, in step 3), the supported metal catalyst is a catalyst in which different metals are supported on different carriers; wherein the supported metal is any one or more of Ag, Mn, Au, Pt, Cu, Ce, Cd, Fe or Co; the loading amount of the metal on the carrier is 0.5 to 5 wt%; the carrier is Al 2 O 3 、Co 3 O 4 、MnO 2 , ZnO, TiO 2 、ZrO 2 、SiO 2 or CeO 2 For example, the supported metal catalyst can be a silver-based catalyst Ag with different carriers and a silver loading of 1 wt%. 1.0 / Y; or Co 3 O 4 Silver-based catalysts with different carriers and silver loadings x / Co 3 O 4 ; or Al 2 O 3 Catalyst A with a carrier and a metal loading of 1 wt% 1.0 / Al 2 O 3 .

[0021] Furthermore, the supported metal catalyst is a particle catalyst, a thin film catalyst or a composite material catalyst.

[0022] Furthermore, the resin matrix is ​​obtained by mixing epoxy resin E51, triethanolamine and KH-540 in a mass ratio of 1:0.224-0.274:0.036-0.044.

[0023] A method for regulating a supported metal catalyst to selectively catalyze and oxidize a reaction product of 5-hydroxymethylfurfural (HMF), wherein the metal catalyst is an Ag-based catalyst Ag x / Y, x represents Ag loading / wt%, and Y represents different carriers; the ratios of 5-hydroxymethyl-2-furancarboxylic acid (HMCA), 5-formyl-2-furancarboxylic acid (FFCA) and 2,5-furandicarboxylic acid (FDCA) in the generated product are regulated by placing the catalyst in hydrogen peroxide for different treatment times before the reaction; increasing the hydrogen peroxide treatment time reduces the proportion of 5-hydroxymethyl-2-furancarboxylic acid in the generated product; reducing the hydrogen peroxide treatment time increases the proportion of 5-hydroxymethyl-2-furancarboxylic acid in the generated product.

[0024] The concentration of hydrogen peroxide is 10-40%, the reaction conditions are 0.1-1Mpa, the temperature is 100-150°C, and the time is 1-10h; after the catalyst is treated, the conductivity of the catalyst is detected by the above-mentioned method of testing, evaluating and regulating the electronic transport performance of the supported metal catalyst.

[0025] The beneficial effects of the present invention are:

[0026] 1. The present invention first mixes the conductive filler, the resin matrix and the catalyst in proportion, and forms a conductive adhesive (ECAs) according to the conductive silver paste curing procedure, and then combines the electron transfer principle, takes the resistivity as an indicator, and adopts a four-probe test method to evaluate the conductive performance of the supported metal catalyst; there is no need to compact the material, the test results are stable, and high-precision conductive performance measurement results can be provided, with a small error range, which can more effectively help understand the electron transfer mechanism of the supported metal catalyst;

[0027] 2. The present application evenly disperses the supported metal catalyst in the silver powder conductive glue, which can provide good conductivity and adhesion; compared with the traditional test method, this method has the advantages of simple steps and stable test results; and the unique advantage of using four-probes to test the conductive properties of the catalyst dispersed in the conductive glue is that this method is applicable to various material forms, including particles, films and composite materials, and the scheme is more applicable;

[0028] 3. This application proposes to 2 O 2 Or other oxidation methods to partially oxidize the metal loaded on the catalyst to change the valence state of the metal active site and the surface electron enrichment, reducing the electron transfer performance between the metal and the carrier, and between the metal and the reactant molecules, thereby achieving the purpose of regulating the catalyst performance;

[0029] 4. This application discloses a new scheme for testing, evaluating and regulating the electron transport performance of supported metal catalysts, which opens up new research ideas and methods for exploring the mechanism of catalytic reactions and the design of new materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The performance comparison of the four samples of Examples 1 to 4 in the selective catalytic oxidation of HMF reaction; reaction conditions: catalyst amount (0.05 g), reactant amount (0.1 mmol), sodium bicarbonate (0.2 mmol), solvent: H 2 O (10 mL), 0.5 MPa O 2 , 120℃, 5h, 600rpm. DETAILED DESCRIPTION

[0031] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0032] Embodiment 1

[0033] Step 1, preparation of resin matrix: epoxy resin E51, triethanolamine and KH-540 were weighed in a mass ratio of 1:0.249:0.04, added into a 50 mL beaker in sequence, stirred manually for 10 min, and then ultrasonicated at room temperature for 15 min to obtain a uniformly mixed resin matrix;

[0034] Step 2: Catalyst treatment: 0.15 g of self-made Ag / Co catalyst with a metal loading of 1 wt% was added. 3 O 4 (Ag 1.0 / Co 3 O 4 ) or Mn / Co with a metal loading of 1 wt% 3 O 4 (Mn 1.0 / Co 3 O 4 ) The catalyst powder was added to 20 mL of 30 wt% H 2 O 2 The aqueous solution was stirred at room temperature for 0 to 4 hours, and then heated in an oil bath at 60°C for 1 hour to obtain H 2 O 2 Treating the supported metal catalyst for 0 to 4 hours;

[0035] Step 3, preparation of conductive silver paste: 0.1 g of the resin matrix prepared in step 1 is placed in a mortar, and then 0.9 g of silver powder (silver powder size is 1-3 μm) is added to the resin matrix and ground for 5 min;

[0036] Step 4: Introduce catalyst: Add 5 wt% of H prepared in step 2 to the conductive silver paste. 2 O 2Ag treated at 0 h 1.0 / Co 3 O 4 (i.e., without oxidation treatment), continue grinding for 15 minutes, apply the ground mixture on a glass slide with a size of 25.4 mm×76.2 mm that has been cleaned and dried, apply it evenly with a scraper, place it in a vacuum drying oven at 175°C for 60 minutes, and cool it naturally to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0037] Step 5. Volume resistivity measurement: A digital micrometer was used to measure the thickness of the prepared conductive adhesive. The average value of 10 points was taken to determine the thickness to determine the test parameters. The volume resistivity ρ (GB / T 31838.2-2019) of the conductive adhesive was tested using an ST-2258C multi-function digital four-probe tester to evaluate the conductive properties of the catalyst.

[0038] Embodiment 2

[0039] Steps 1 to 3 are the same as the corresponding steps in Example 1;

[0040] Step 4: Introduce catalyst: Add 5 wt% of H prepared in step 2 to the conductive silver paste. 2 O 2 Ag treated for 1h 1.0 / Co 3 O 4 , continue grinding for 15 minutes, apply the ground mixture on a glass slide with a size of 25.4 mm × 76.2 mm that has been cleaned and dried, apply it evenly with a scraper, place it in a vacuum drying oven at 175°C for 60 minutes, and cool it naturally to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0041] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0042] Embodiment 3

[0043] Steps 1 to 3 are the same as the corresponding steps in Example 1;

[0044] Step 4: Introduce catalyst: Add 5 wt% of H prepared in step 2 to the conductive silver paste. 2 O 2 Ag treated for 2h 1.0 / Co 3 O 4 , continue grinding for 15 minutes, apply the ground mixture on a glass slide with a size of 25.4 mm × 76.2 mm that has been cleaned and dried, apply it evenly with a scraper, place it in a vacuum drying oven at 175°C for 60 minutes, and cool it naturally to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0045] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0046] Embodiment 4

[0047] Steps 1 to 3 are the same as the corresponding steps in Example 1;

[0048] Step 4: Introduce catalyst: Add 5 wt% of H prepared in step 2 to the conductive silver paste. 2 O 2 Ag treated for 4 h 1.0 / Co 3 O 4 , continue grinding for 15 minutes, apply the ground mixture on a glass slide with a size of 25.4 mm × 76.2 mm that has been cleaned and dried, apply it evenly with a scraper, place it in a vacuum drying oven at 175°C for 60 minutes, and cool it naturally to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0049] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0050] Embodiment 5

[0051] Steps 1 to 3 are the same as the corresponding steps in Example 1;

[0052] Step 4: Introduce catalyst: Add 5 wt% of H prepared in step 2 to the conductive silver paste. 2 O 2 Treatment 0h Mn 1.0 / Co 3 O 4 (i.e., without oxidation treatment), continue grinding for 15 minutes, apply the ground mixture on a glass slide with a size of 25.4 mm×76.2 mm that has been cleaned and dried, apply it evenly with a scraper, place it in a vacuum drying oven at 175°C for 60 minutes, and cool it naturally to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0053] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0054] Embodiment 6

[0055] Steps 1 to 3 are the same as the corresponding steps in Example 1;

[0056] Step 4: Introduce catalyst: Add 5 wt% of H prepared in step 2 to the conductive silver paste. 2 O 2 Mn treated for 1h 1.0 / Co 3 O 4), continue grinding for 15 minutes, apply the ground mixture on a glass slide with a size of 25.4 mm×76.2 mm and washed and dried, apply it evenly with a scraper, place it in a vacuum drying oven at 175° C. for 60 minutes, and cool it naturally to room temperature to obtain a conductive glue filled with a supported metal catalyst;

[0057] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0058] Embodiment 7

[0059] Step 1, step 2 and step 3 are the same as the corresponding steps in embodiment 1;

[0060] Step 4: Introduce catalyst: Add 5 wt% of H prepared in step 2 to the conductive silver paste. 2 O 2 Mn treated for 2h 1.0 / Co 3 O 4 , continue grinding for 15 minutes, apply the ground mixture on a glass slide with a size of 25.4 mm × 76.2 mm that has been cleaned and dried, apply it evenly with a scraper, place it in a vacuum drying oven at 175°C for 60 minutes, and cool it naturally to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0061] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0062] Embodiment 8

[0063] Step 1, step 2 and step 3 are the same as the corresponding steps in embodiment 1;

[0064] Step 4: Introduce catalyst: Add 5 wt% of H prepared in step 2 to the conductive silver paste. 2 O 2 Mn treated for 4 hours 1.0 / Co 3 O 4 , continue grinding for 15 minutes, apply the ground mixture on a glass slide with a size of 25.4 mm × 76.2 mm that has been cleaned and dried, apply it evenly with a scraper, place it in a vacuum drying oven at 175°C for 60 minutes, and cool it naturally to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0065] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0066] Embodiment 9

[0067] Step 1, preparation of resin matrix: the same as the corresponding step in Example 1;

[0068] Step 2: Preparation of catalyst: Prepare the metal precursor AgNO 3 (AR) was dissolved in deionized water, and then Co was added to the solution. 3 O 4 The powder was stirred at 600 rpm at 60 °C until it was dry powder; after impregnation, all samples were dried at 80 °C under vacuum for 6 h; finally, the catalyst with the corresponding Ag loading (Ag x / Co 3 O 4 ), where x represents the Ag loading amount, and its value is 0.5, 1, 2, 3, and the unit is wt%.

[0069] Step 3, preparation of conductive silver paste: the same as the corresponding step in Example 1;

[0070] Step 4: Introduce catalyst: Add 5 wt% of Ag prepared in step 2 to the conductive silver paste. 0.5 / Co 3 O 4 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0071] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0072] Embodiment 10

[0073] Steps 1 to 3 are the same as the corresponding steps of Example 9;

[0074] Step 4: Introduce catalyst: Add 5 wt% of Ag prepared in step 2 to the conductive silver paste. 1.0 / Co 3 O 4 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0075] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0076] Embodiment eleven:

[0077] Steps 1 to 3 are the same as the corresponding steps of Example 9;

[0078] Step 4: Introduce catalyst: Add 5 wt% of Ag prepared in step 2 to the conductive silver paste. 2.0 / Co 3 O 4 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0079] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0080] Embodiment 12

[0081] Steps 1 to 3 are the same as the corresponding steps of Example 9;

[0082] Step 4: Introduce catalyst: Add 5 wt% of Ag prepared in step 2 to the conductive silver paste. 3.0 / Co 3 O 4 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0083] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0084] Embodiment 13

[0085] Step 1, preparation of resin matrix: the same as the corresponding step in Example 1;

[0086] Step 2: Preparation of catalyst: Prepare the metal precursor AgNO 3 (AR) was dissolved in deionized water, and then carrier powder (ZnO, CeO 2 、MnO 2 、ZrO 2 、TiO 2 、Al 2 O 3 、SiO 2 ), stirred at 600 rpm at 60°C until dry powder; after impregnation, all samples were dried at 80°C under vacuum for 6 h; finally, kept at 550°C in static air for 5 h (heating rate of 3°C / min), and a silver-based catalyst with a Ag loading of 1 wt% but different carriers (Ag 1.0 / Y), wherein Y represents a different vector.

[0087] Step 3, preparation of conductive silver paste: the same as the corresponding step in Example 1;

[0088] Step 4: Introduce catalyst: Add 5 wt% of Ag prepared in step 2 to the conductive silver paste. 1.0 / MnO 2 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0089] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0090] Embodiment 14

[0091] Steps 1 to 3 are the same as the corresponding steps in Example 13;

[0092] Step 4: Introduce catalyst: Add 5 wt% of Ag prepared in step 2 to the conductive silver paste. 1.0 / ZnO was ground for 15 minutes, and the ground mixture was coated on a glass slide with a size of 25.4 mm × 76.2 mm that had been cleaned and dried, and coated evenly with a scraper, placed in a vacuum drying oven at 175°C for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0093] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0094] Embodiment 15

[0095] Steps 1 to 3 are the same as the corresponding steps in Example 13;

[0096] Step 4: Introduce catalyst: Add 5 wt% of Ag prepared in step 2 to the conductive silver paste. 1.0 / TiO 2 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0097] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0098] Embodiment 16

[0099] Steps 1 to 3 are the same as the corresponding steps in Example 13;

[0100] Step 4: Introduce catalyst: Add 5 wt% of Ag prepared in step 2 to the conductive silver paste. 1.0 / ZrO 2 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0101] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0102] Embodiment 17

[0103] Steps 1 to 3 are the same as the corresponding steps in Example 13;

[0104] Step 4: Introduce catalyst: Add 5 wt% of Ag prepared in step 2 to the conductive silver paste. 1.0 / SiO 2 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0105] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0106] Embodiment 18

[0107] Steps 1 to 3 are the same as the corresponding steps in Example 13;

[0108] Step 4: Introduce catalyst: Add 5 wt% of Ag prepared in step 2 to the conductive silver paste. 1.0 / CeO 2 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0109] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0110] Embodiment 19

[0111] Steps 1 to 3 are the same as the corresponding steps in Example 13;

[0112] Step 4: Introduce catalyst: Add 5 wt% of Ag prepared in step 2 to the conductive silver paste. 1.0 / Al 2 O 3 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0113] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0114] Comparative Example 1

[0115] Step 1 is the same as the corresponding step in Example 1;

[0116] Step 2: 0.1 g of the resin matrix prepared in step 1 was placed in a mortar, and 0.9 g of silver powder was added to the resin matrix and ground for 20 min. Next, the ground mixture was coated on a cleaned glass slide with a size of 25.4 mm × 76.2 mm, and the surface was smoothed with a scraper. The mixture was placed in a vacuum drying oven at 175°C for 60 min, and then cooled naturally to room temperature to obtain a conductive adhesive (ECA) filled with a non-loaded metal catalyst. original ).

[0117] Step 3: Volume resistivity measurement: the same as step 5 of embodiment 1.

[0118] Comparative Example 2

[0119] Step 1, preparation of resin matrix: the same as the corresponding step of Example 1;

[0120] Step 2, preparation of conductive silver paste: the same as step 3 of Example 1;

[0121] Step 3: Introduce carrier: Add 5wt% Co to the conductive silver paste 3 O 4 The grinding was continued for 15 minutes, and the ground mixture was coated on a cleaned glass slide with a size of 25.4 mm×76.2 mm. After being flattened by a scraper, the mixture was placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a carrier material.

[0122] Step 4: Volume resistivity measurement: the same as step 5 of embodiment 1.

[0123] Comparative Example 3

[0124] Step 1, preparation of resin matrix: the same as the corresponding step of Example 1;

[0125] Step 2, preparation of conductive silver paste: the same as step 3 of Example 1;

[0126] Step 3: Introduce carrier: Add 5wt% Al into the conductive silver paste 2 O 3 The grinding was continued for 15 minutes, and the ground mixture was coated on a cleaned glass slide with a size of 25.4 mm×76.2 mm. After being flattened by a scraper, the mixture was placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a carrier material.

[0127] Step 4: Volume resistivity measurement: the same as step 5 of embodiment 1.

[0128] Table 1, H 2 O 2 Processed Ag 1.0 / Co 3 O 4 Volume Resistivity Data of Catalyst Filled Conductive Adhesives

[0129]

[0130] From the data in Table 1, we can see that compared with the 2 O 2 The treated catalyst is a conductive glue with a conductive carrier, with H 2 O 2 Processed Ag 1.0 / Co 3 O 4 The conductive performance of the conductive glue with the catalyst as the conductive carrier decreased after testing, and as H 2 O 2 The increase in processing time, Ag 1.0 / Co 3 O 4 The number of oxidation states of Ag in the metal increases, the number of free valence electrons decreases, and the reducibility of the metal decreases, which weakens its electron transfer ability and causes its conductive properties to decrease.

[0131] The catalytic performance of the corresponding Ag-based catalysts is shown in Figure 1 As shown in the figure, the selective catalytic oxidation of HMF to DFF / HMCA, FFCA and FDCA is an important type of biomass platform molecule high value reaction. Ag-based catalysts can 2 O 2 After the treatment, some free electrons were lost, and the reaction rate at the active center decreased, which was manifested as a decrease in HMF conversion and HMCA generation, while the production of downstream products such as FFCA increased. These results prove that the catalyst's electron transfer ability has decreased and oxidation treatment can adjust its catalytic performance.

[0132] Table 2, H 2 O 2 Treated Mn1.0 / Co 3 O 4 Volume Resistivity Data of Catalyst Filled Conductive Adhesives

[0133]

[0134] From the data in Table 2, we can see that: 2 O 2 Treated Mn 1.0 / Co 3 O 4 The conductivity of the conductive glue with catalyst as conductive carrier is better than that of the conductive glue without H 2 O 2 The conductive properties of the conductive glue with the treated catalyst as the conductive carrier decreased, and with the increase of H 2 O 2 The increase of processing time, Mn 1.0 / Co 3 O 4 The oxidation state and number of Mn in the metal increase, the number of free valence electrons decreases, and the reducibility of the metal decreases, which weakens its electron transfer ability and causes its conductivity to decrease.

[0135] Table 3. Ag with different Ag loadings x / Co 3 O 4 Volume Resistivity Data of Catalyst Filled Conductive Adhesives

[0136]

[0137]

[0138] From the data in Table 3, it can be seen that the Ag with different Ag loading amounts x / Co 3 O 4 The conductive glue with the catalyst as the conductive carrier has a higher conductivity than the conductive glue doped with the pure carrier (Comparative Example 2). x / Co 3 O 4 Ag in the catalyst provides more electron donors and acceptors for the metal catalyst, thereby accelerating the electron transfer process, enhancing its electron transfer ability, and causing its conductive properties to increase accordingly.

[0139] Table 4. Volume resistivity data of conductive glue filled with catalysts loaded with 1 wt% Ag on different supports

[0140]

[0141] From the data in Table 4, it can be seen that the metal catalysts filled with different carriers have different effects on the volume resistivity of the conductive glue. 2 , ZnO, TiO 2 Compared with the conductive glue without loaded metal catalyst, the volume resistivity of the conductive glue filled with loaded metal catalyst as carrier increased by 151.8%, 78.8% and 8.5%, respectively, which reduced the overall conductive performance of ECAs. The above results show that the volume resistivity of ECAs filled with loaded metal catalyst as carrier increased by 151.8%, 78.8% and 8.5%, respectively, which reduced the overall conductive performance of ECAs. 2 , ZnO, TiO 2 The electron transport ability of supported metal catalysts in conductive glue is relatively weak. 2 、SiO 2 、CeO 2 、Al 2 O 3 Compared with the conductive glue without loaded metal catalyst, the volume resistivity of the conductive glue filled with loaded metal catalyst as carrier decreased by 18.2%, 4.9%, 6.8% and 3.0% respectively, which improved the overall conductive performance of ECAs. The above results show that the volume resistivity of ECAs filled with loaded metal catalyst as carrier decreased by 18.2%, 4.9%, 6.8% and 3.0% respectively, which improved the overall conductive performance of ECAs. 2 、SiO 2 、CeO 2 、Al 2 O 3 The supported metal catalyst as a carrier has a relatively strong electron transport capability in the conductive glue.

[0142] Considering the different carriers in the series of catalyst filled conductive glue, Ag 1.0 / Al 2 O 3 The volume resistivity of the conductive adhesive filled with catalyst is the lowest. 2 O 3 A series of catalyst-filled conductive gels loaded with different metals were prepared as supports to evaluate the electron transport properties of the catalysts.

[0143] Embodiment 20

[0144] Step 1, preparation of resin matrix: the same as the corresponding step of Example 1;

[0145] Step 2: Preparation of catalyst: Different metal precursors (HAuCl 4 ·4H 2 O, H 2 PtCl 6 6H 2 O, Cu(NO 3 ) 2 ·3H 2 O、Ce(NO 3 )3 6H 2 O、Cd(CH 3 COOH) 2 ·2H 2 O, FeCl 3 、Co(NO) 3 6H 2 O)) was dissolved in deionized water, and then Al was added to the solution 2 O 3 The carrier powder was stirred at 600 rpm at 60°C until it was dry powder. After impregnation, all samples were dried at 80°C in a vacuum environment for 6 h. Finally, static air was maintained at 550°C for 5 h (heating rate was 3°C / min) to obtain Al 2 O 3 The catalyst (X 1.0 / Al 2 O 3 ), where X represents different metals such as Au, Pt, Cu, Ce, Cd, Fe, and Co.

[0146] Step 3: Preparation of conductive silver paste: the same as the corresponding step in Example 1;

[0147] Step 4: Introduce catalyst: Add 5 wt% of Au prepared in step 2 to the conductive silver paste. 1.0 / Al 2 O 3 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0148] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0149] Embodiment 21

[0150] Steps 1 to 3 are the same as the corresponding steps of Example 20;

[0151] Step 4: Introduce catalyst: Add 5 wt% of Fe prepared in step 2 to the conductive silver paste. 1.0 / Al 2 O 3 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0152] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0153] Embodiment 22

[0154] Steps 1 to 3 are the same as the corresponding steps of Example 20;

[0155] Step 4: Introduce catalyst: Add 5 wt% of Ce prepared in step 2 to the conductive silver paste. 1.0 / Al 2 O 3 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0156] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0157] Embodiment 23

[0158] Steps 1 to 3 are the same as the corresponding steps of Example 20;

[0159] Step 4: Introduce catalyst: Add 5 wt% of Co prepared in step 2 to the conductive silver paste. 1.0 / Al 2 O 3 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0160] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0161] Embodiment 24

[0162] Steps 1 to 3 are the same as the corresponding steps of Example 20;

[0163] Step 4: Introduce catalyst: Add 5 wt% of Cu prepared in step 2 to the conductive silver paste. 1.0 / Al 2 O 3 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0164] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0165] Embodiment 25

[0166] Steps 1 to 3 are the same as the corresponding steps of Example 20;

[0167] Step 4: Introduce catalyst: Add 5 wt% of Pt prepared in step 2 to the conductive silver paste. 1.0 / Al 2 O 3 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0168] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0169] Embodiment 26

[0170] Steps 1 to 3 are the same as the corresponding steps of Example 20;

[0171] Step 4: Introduce catalyst: Add 5 wt% of Cd prepared in step 2 to the conductive silver paste. 1.0 / Al 2 O 3 The mixture was ground for 15 minutes, and then coated on a cleaned and dried glass slide with a size of 25.4 mm × 76.2 mm, and evenly coated with a scraper, and placed in a vacuum drying oven at 175° C. for 60 minutes, and naturally cooled to room temperature to obtain a conductive adhesive filled with a supported metal catalyst;

[0172] Step 5: Volume resistivity measurement: the same as the corresponding step in Example 1.

[0173] Table 5, Al 2 O 3 Volume resistivity data of conductive glue filled with catalysts loaded with 1wt% different metals as carrier

[0174]

[0175]

[0176] It can be seen from Table 5 that: 2 O 3The volume resistivity of the conductive glue filled with catalysts with different metals as carriers and 1wt% loading was affected differently. The volume resistivity of the silver powder conductive glue filled with catalysts loaded with Au, Pt, Cu, Ce, Cd, Fe, and Co decreased by 8.9%, 27.6%, 22.1%, 16%, 27.9%, 9.5%, and 19.2% respectively compared with the resistivity of the silver powder conductive glue without catalyst, which improved the overall conductivity of ECAs.

[0177] Compared with pure Al, the conductive glue filled with Au, Ce, and Fe supported metal catalysts 2 O 3 The volume resistivity of the filled conductive glue increased by 10.8%, 10%, and 2.2%, respectively; and the conductive glue filled with supported metal catalysts loaded with Co, Cu, Pt, and Cd was higher than that of pure carrier Al. 2 O 3 The volume resistivity of the conductive adhesive filled with Al decreased by 1.8%, 5.4%, 12.2% and 12.5% ​​respectively. 2 O 3 The electron transfer capabilities of catalysts with different metals as carriers and loaded with 1wt% of different metals are different. The electron transfer between metal and carrier, metal and metal, and carrier and carrier in the supported metal catalyst will directly affect its electron transfer performance.

[0178] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.

Claims

1. A method for testing, evaluating and regulating the electron transport performance of a supported metal catalyst, characterized in that: The steps include: 1) preparing a resin matrix; 2) preparing a conductive adhesive: adding a conductive filler into the resin matrix prepared in step 1) and grinding the mixture thoroughly and evenly; 3) adding a supported metal catalyst to the conductive adhesive and grinding it, coating it evenly on a glass slide, heating and curing it, and cooling it to room temperature to obtain a conductive adhesive filled with a supported metal catalyst; 4) Volume resistivity measurement: The thickness of the conductive glue was measured, and the volume resistivity ρ of the conductive glue was tested using a four-probe tester for analysis and comparison to evaluate the electron transport performance of different supported catalysts.

2. A method for testing, evaluating and regulating the electron transport performance of a supported metal catalyst according to claim 1, characterized in that: In step 1), the resin matrix is ​​obtained by uniformly mixing a resin raw material, a curing agent and a coupling agent, and the resin raw material is one or more of epoxy resin, silicone resin, acrylic resin and phenolic resin.

3. A method for testing, evaluating and regulating the electron transport performance of a supported metal catalyst according to claim 1, characterized in that: In step 2), the mass ratio of the resin matrix to the conductive filler is 1-4:6-9, and the conductive filler used is any one or more of silver, gold, nickel, copper, aluminum, tin, lead, indium, zinc, and iron.

4. A method for testing, evaluating and regulating the electron transport performance of a supported metal catalyst according to claim 1, characterized in that: In step 3), after the supported metal catalyst is added to the conductive adhesive, the weight percentage of the supported metal catalyst is 1 to 10 wt %.

5. A method for testing, evaluating and regulating the electron transport performance of a supported metal catalyst according to claim 1, characterized in that: In step 3), the grinding time is 10 to 20 minutes, the heating and curing temperature is 170 to 180° C., and the heating and curing time is 60 minutes.

6. A method for testing, evaluating and regulating the electron transport performance of a supported metal catalyst according to claim 1, characterized in that: In step 3), the method for regulating the electron transport performance of the supported metal catalyst is to perform an oxidation treatment on the supported metal catalyst, and the oxidation treatment method includes oxidation using H2O2, O2 or air.

7. A method for testing, evaluating and regulating the electron transport performance of a supported metal catalyst according to claim 1, characterized in that: In step 3), the supported metal catalyst is a catalyst with different metals supported on different carriers; wherein the supported metal is any one or more of Ag, Mn, Au, Pt, Cu, Ce, Cd, Fe or Co; the loading amount of the metal on the carrier is 0.5-5wt%; the carrier is any one or more of Al2O3, Co3O4, MnO2, ZnO, TiO2, ZrO2, SiO2 or CeO2.

8. A method for testing, evaluating and regulating the electron transport performance of a supported metal catalyst according to claim 1, characterized in that: The supported metal catalyst is a particle catalyst, a film catalyst or a composite material catalyst.

9. A method for regulating a supported metal catalyst to selectively catalyze and oxidize a reaction product of 5-hydroxymethylfurfural, characterized in that: The metal catalyst is an Ag-based catalyst. x / Y, x represents the Ag loading amount / wt%, and Y represents different carriers. The ratio of 5-hydroxymethyl-2-furancarboxylic acid, 5-formyl-2-furancarboxylic acid and 2,5-furandicarboxylic acid in the generated product is regulated by placing the catalyst in hydrogen peroxide for different treatment times before the reaction; when the treatment time is increased, the proportion of 5-hydroxymethyl-2-furancarboxylic acid in the generated product decreases, and when the treatment time is reduced, the proportion of 5-hydroxymethyl-2-furancarboxylic acid in the generated product increases.

10. The method according to claim 9, characterized in that The concentration of hydrogen peroxide is 10-40%, the reaction conditions are 0.1-1Mpa, the temperature is 100-150°C, and the time is 1-10h; after the catalyst is treated, the volume resistivity of the catalyst is detected by the method for testing and evaluating the electronic transport performance of the supported metal catalyst according to claim 1.

Citation Information

Patent Citations

  • Method for detecting electrical conductivity of small number of solids

    CN103852642A